Public Opinion on Criminal Trial Proceedings in China: An Examination of a Capital Case - Bin Liang; Jiaqi Yan; Ming Hu; Hua Zhong (Modern China, 2026)
Historically, opportunities for members of the public in China to observe criminal trials have been limited. Other than jurors and lay judges (“people’s assessors”), the public has rarely had opportunities to observe criminal trial proceedings in person. Along with China’s reform measures to increase judicial transparency, the move to broadcasting trials online via platforms like China Court Trial Online offers an invaluable opportunity for the public to observe trials. In this study, a fully recorded homicide trial in mainland China was shown to students enrolled in law majors (n=97) and non-law majors (n=86) from one Chinese university. Their evaluations of the trial proceedings were subsequently surveyed. This is the first known study that allows members of the public to watch a full-length trial and provide their assessments of criminal trial proceedings in China. The issues reported by students echo problems identified by scholars and shed significant light on potential lessons to be learned from public observation of Chinese criminal trials.